Personalized ex vivo multiple peptide enrichment and detection of T cells reactive to multiple tumor-associated antigens in prostate cancer patients - Taborska, Pavla; Stakheev, Dmitry; Strizova, Zuzana; Vavrova, Katerina; Podrazil, Michal; Bartunkova, Jirina; Smrz, Daniel (Medical oncology (Northwood, London, England), 2017)
Personalized peptide vaccination is a promising immunotherapeutic approach in prostate cancer (PCa). We therefore examined whether an approach, utilizing personalized multiple peptide-mediated ex vivo enrichment with effector T cells reactive to multiple tumor-associated antigens (TAAs), could be employed as a basis for the development of T cell immunotherapy of PCa. In this study, we used the non-adherent fraction (lymphocytes) of cryopreserved peripheral blood mononuclear cells from a leukapheretic product of biochemically recurrent (BR, n = 14) and metastatic hormone-refractory (HR, n = 12) PCa patients. The lymphocytes were primed with a pool of mixed overlapping peptides derived from 6 PCa TAAs-PSA, PAP, NY-ESO-1, MAGE-A1, MAGE-A3 and MAGE-A4. After 2 weeks of culture, the cells were stimulated with the peptides and T cell reactivity determined by externalization of CD107a. No TAAs-reactive effector T cells were detected in the patient's lymphocytes after their reconstitution. However, following their priming with the TAAs-derived peptides and 2-week culturing, the lymphocytes became enriched with polyclonal TAAs-reactive effector CD8+ T cells in 8 out of 14 BR and 5 out of 12 HR patients. No such reactive CD8+ T cells were detected in cultured lymphocytes without the peptide priming. Stimulation of the responding cultures with peptides derived from individual TAAs revealed a unique repertoire of the reactive CD8+ T cells. Our strategy revealed that the personalized multiple peptide-mediated ex vivo enrichment with multiple TAAs-reactive T cells in the PCa patient's lymphocytes is a viable approach for development of T cell immunotherapy of PCa.
Keywords: Prostatic Neoplasms; Membrane Proteins; nádory prostaty; nádorové proteiny; Humans; Prostate cancer; CD107a externalization; lidé středního věku; T-Lymphocytes; Precision Medicine; Melanoma-Specific Antigens; Aged; kalikreiny; Leukocytes, Mononuclear; Prostate-Specific Antigen; senioři; lidé; individualizovaná medicína; Immunotherapy; Cells, Cultured; Antigens, Neoplasm; Personalized T cell immunotherapy; peptidy; CD8-Positive T-Lymphocytes; antigeny nádorové; CD8-pozitivní T-lymfocyty; Peptides; Male; Middle Aged; prostatický specifický antigen; kultivované buňky; membránové proteiny; leukocyty mononukleární; T-lymfocyty; melanomové antigeny; Tumor-associated antigens; Neoplasm Proteins; mužské pohlaví; imunoterapie; Kallikreins